2016
DOI: 10.1109/tip.2016.2548247
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Flow-Based Full Reference Video Quality Assessment Algorithm

Abstract: We present a simple yet effective optical flow-based full-reference video quality assessment (FR-VQA) algorithm for assessing the perceptual quality of natural videos. Our algorithm is based on the premise that local optical flow statistics are affected by distortions and the deviation from pristine flow statistics is proportional to the amount of distortion. We characterize the local flow statistics using the mean, the standard deviation, the coefficient of variation (CV), and the minimum eigenvalue ( λ min )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…The success of VQA algorithms should depend on their abilities to model motion perception in the HVS. Manasa et al [26] estimated the temporal distortion by the use of the mean, the standard deviation, the coefficient of variation, and the minimum eigenvalue of local optical flow statistics. In addition, experiments demonstrated that local flow statistics are effective features for assessing temporal quality.…”
Section: Motivationsmentioning
confidence: 99%
“…The success of VQA algorithms should depend on their abilities to model motion perception in the HVS. Manasa et al [26] estimated the temporal distortion by the use of the mean, the standard deviation, the coefficient of variation, and the minimum eigenvalue of local optical flow statistics. In addition, experiments demonstrated that local flow statistics are effective features for assessing temporal quality.…”
Section: Motivationsmentioning
confidence: 99%
“…Regarding the objective quality metrics for audio, these include PEAQ (Perceived Evaluation of Audio Quality) [14], POLQA Music (Perceptual Objective Listening Quality Assessment) [15,16], and ViSQOL Audio (Virtual Speech Quality Objective Listener) [17]. For video, a whole range of quality metrics exist, such as PEVQ (Perceptual Evaluation of Video Quality) [18], VQM (Video Quality Metric) [19], ST-MAD (Spatiotemporal Most-Apparent Distortion model) [20], MOVIE (Motion-based Video Integrity Evaluation) [21], ST-RRED (Spatiotemporal Reduced Reference Entropic Differences) [22], and FLOSIM [23], among others. It is also common to adapt Image Quality Metrics, such as PSNR (Peak Signal-to-Noise Ratio) and MS-SSIM [24] using the average of frame-wise measurements.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Various other FR metrics have been proposed in the literature [12]. Aabed et al [13] proposed a perceptual quality metric that utilises low complexity power spectral features in the frequency domain, while Manasa and Channappayya [14] proposed the use of optical flow statistics, such as the minimum eigenvalue of the local flow patches, the mean, the standard deviation, and the coefficient of variation in order to estimate temporal quality and the use of SSIM for spatial quality estimation, combining both for computing the final quality score. Seshadrinathan and Bovik [15] proposed the MOVIE index that examines temporal, spatial, and spatiotemporal characteristics of distortion in order to estimate video quality.…”
Section: Full-reference Metricsmentioning
confidence: 99%